2021
DOI: 10.1037/cbs0000253
|View full text |Cite
|
Sign up to set email alerts
|

Explaining support for post-secondary educational funding for indigenous students.

Abstract: A concerning post-secondary education gap exists between Indigenous and non-Indigenous individuals in Canada. One program designed to help address this issue, the Post-Secondary Student Support Program (PSSSP), provides eligible First Nations students with post-secondary education funding. Although such programs are beneficial, it is unclear how much Canadians support public funding of Indigenous education and whether psychological research can help explain why some may endorse or oppose it. Thus, using the PS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
(89 reference statements)
0
3
0
Order By: Relevance
“…Political Orientation -We assessed political orientation in general, fiscally and socially (3-items, α = .944), similar to prior research (e.g., Genge & Day, 2021). Responses were indicated along a liberal to conservative scale (1 = very liberal, 7 = very conservative), with additional responses (for general: 8 = don't know/not political, 9 = libertarian, 10 = other; and for fiscal and social: 8 = other).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Political Orientation -We assessed political orientation in general, fiscally and socially (3-items, α = .944), similar to prior research (e.g., Genge & Day, 2021). Responses were indicated along a liberal to conservative scale (1 = very liberal, 7 = very conservative), with additional responses (for general: 8 = don't know/not political, 9 = libertarian, 10 = other; and for fiscal and social: 8 = other).…”
Section: Methodsmentioning
confidence: 99%
“…Responses were based on a sample of 212 Canadian participants recruited from Prolific for prior research(Genge & Day, 2021). The study was titled "Opinions of People and Programs in Canada. "…”
mentioning
confidence: 99%
“…Positive attitudes toward minority groups were associated with greater support for policies related to restorative action toward disadvantaged groups in Spain and Canada (Urbiola et al, 2017). When policies pertain to more specific actions or programs targeting marginalized groups, Genge and Day (2021) found that non-Indigenous individuals who expressed prejudicial attitudes toward Indigenous Peoples were more likely to express lower support for a program aimed at providing postsecondary funding support to Indigenous students. Moreover, research conducted by Dixon et al (2010) examined the mediating role of prejudice in the relationship between intergroup contact and disagreement of policies benefitting marginalized groups.…”
Section: Intergroup Contact Attitudes and Policy Supportmentioning
confidence: 99%